Nanomaterials chemistry recent developments and new directions - Cheetham, A. K.; Müller, Achim 1938-; Rao, C. N. R. (Chintamani Nagesa Ramachandra) 1934- (Wiley-VCH, 2007)
With this handbook, the distinguished team of editors has combined the expertise of leading nanomaterials scientists to provide the latest overview of this field. They cover the whole spectrum of nanomaterials, ranging from theory, synthesis, properties, characterization to application, including such new developments as quantum dots, nanoparticles, nanoporous materials, nanowires, nanotubes, and nanostructured polymers.